Response of Growth and Yield of Several Varieties of Lettuce Plants (Lactuca sativa L.) at Different Concentrations of Nutrients with Smart Aeroponic System - Akbar, Muhammad; Kurniasih, Ratih; Kanny, Putri Irene; Farhah, Najmi (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Lettuce cultivation is usually done conventionally and then transferred into a more controlled and efficient cultivation environment, one of which is using an aeroponic system. This study aimed to determine the Effect of different nutrient concentrations on the growth and yield of lettuce and the Effect of different varieties nested in nutrient concentrations on the growth and yield of lettuce with aeroponic systems. This research was conducted in March-July 2024 at Gunadarma University Technopark (UG-Technopark). The design used is RCBD Nested Design consisting of 2 factors (2x4), factor I AB Mix nutrient concentration (K), consisting of 2 levels of 1200 ppm (K1) and 1800 ppm (K2). Factor II, which is nested in factor I, is lettuce variety (V) consisting of 4 levels, namely Kriebo variety (V1), Karina variety (V2), Bisi SL 02 variety (V3), and Grand Rapids variety (V4). Each was repeated 4 times, so there were 32 experimental units. The results showed that differences in nutrient concentrations had a significant effect on the parameters of plant height, number of leaves, leaf length, root length, header dry weight, root wet weight and root header ratio. The best nutrient concentration was obtained at 1800 ppm AB Mix concentration. The difference in varieties nested in nutrient concentrations has a significant effect on the growth and yield of lettuce, the parameters of plant height of the Grand Rapids variety, number of leaves of Karina variety, leaf length of Bisi SL 02 variety, root length of Karina variety, header wet weight of Kriebo variety, root dry weight of Karina variety and root header ratio of Kriebo variety nested in 1800 ppm nutrient concentration.